Análise das notificações de leptospirose em crianças e adolescentes atendidas em hospital referência de Santa Catarina de 2016 a 2021 - Bruna Rúbia Carvalho de Souza; Emanuela da Rocha Carvalho (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: To identify the epidemiological leptospirosis profile in the pediatric population (0 to 15 years old), as well as to analyze and review clinical data, in order to contribute with public health policy strategies and point out the importance of leptospirosis and its notification by the health authorities. METHODS: An epidemiological, observational, analytical and cross-sectional study of 101 leptospirosis notification forms, CID10- A27.9, notified by epidemiological surveillance nucleus of a tertiary pediatric hospital, from January 2016 to December 2021, this research was submitted and approved by the institutions Ethics Committee. RESULTS: Of the 101 notifications, 13 (12.9%) had clinical and laboratory diagnostic confirmation for leptospirosis, 12 (92.3%) in males, from peri-urban areas; the greatest source of exposure was river, stream, lagoon or dam representing 7 (53.8%) cases. CONCLUSION: The predominant profile is a boy, resident of the peri-urban area, the clinical has nonspecific and self-limited symptoms.